Cervical lymph node metastases is not an uncommon finding in Ga-68-DKFZ-PSMA-11 PET/CT imaging in patients with prostate cancer - Nematyazar, J.; Sahin, O. E.; Razavi, B.; Demirci, E.; Aygun, A.; Ocak, M.; Obek, C.; Kural, A. R.; Kabasakal, L. (SPRINGER, 2015)
28th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM), Hamburg, GERMANY, OCT 10-14, 2015